2009
DOI: 10.1177/0145445509348056
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Virtual Environments for Eliciting Emotional Responses in Patients With Eating Disorders and in Controls

Abstract: This article explores the efficacy of virtual environments representing situations that are emotionally significant to patients with eating disorders (ED) to modify depression and anxiety levels both in these patients and in controls. Eighty-five ED patients and 108 students were randomly exposed to five experimental virtual environments (a kitchen with low-calorie food, a kitchen with high-calorie food, a restaurant with high-calorie food, a restaurant with low-calorie food, and a swimming-pool) and to one ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 57 publications
5
61
0
1
Order By: Relevance
“…In recent years, studies have shown that exposure to virtual food produces the same sensations as exposure to real food, using both non-immersive [24] and immersive environments [25].…”
Section: Virtual Reality As a Clinical Toolmentioning
confidence: 99%
“…In recent years, studies have shown that exposure to virtual food produces the same sensations as exposure to real food, using both non-immersive [24] and immersive environments [25].…”
Section: Virtual Reality As a Clinical Toolmentioning
confidence: 99%
“…The main clinical studies that have used VR environments in their application to different mental disorders have focused on evaluating the usefulness of these scenarios for generating the behavioral, cognitive and emotional reactions in the person immersed in the virtual world that these same contexts would produce in real life, something which has been widely proven in the many applications studied (e.g., Bordnick et al, 2008;Ferrer-García et al, 2009;Culbertson et al, 2010). Moreover, a large number of studies have concentrated on comparing the effectiveness of this new type of treatment with VR with the usual interventions used, and to date, many case studies, non-systematic studies and controlled studies have shown the effectiveness of VR treatments in a wide range of disorders, such as anxiety, eating disorders, or in addictions, among other alterations (Gutiérrez-Maldonado, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Others have demonstrated that virtual environments involving high-caloric food elicit strong emotional responses in ED patients [41], reflecting a fear of gaining weight and an over-evaluation of weight and shape. ED patients also report higher anxiety and depressive symptoms in virtual environments where they virtually eat high-energy food [42]. Another significant environment for ED patients is the swimming pool environment.…”
Section: Efficacy Of Virtual Reality Focusing On Body Image In Ed Womenmentioning
confidence: 99%
“…Another significant environment for ED patients is the swimming pool environment. [41,42]. According to Thompson and Chad [43], the high emotional reaction observed in the pool environment also reflects the over-evaluation of weight and shape in ED women.…”
Section: Efficacy Of Virtual Reality Focusing On Body Image In Ed Womenmentioning
confidence: 99%
See 1 more Smart Citation